The moral economy of comfortable living: Negotiating individualism and collectivism through housing in Belgrade. (June 2018) - Johnson, Charlotte E
Comfort in the home depends on material and social connections. From pipes and wires to legal and financial contracts, these connections shape expectations of what comfortable living is and how it can be achieved. These connections create a moral economy that is based on the materiality of housing, and that is revealed as individual households pursue comfortable conditions in reference to external criteria and constraints. This paper explores the moral economy of comfort through an ethnography of one apartment block in Belgrade. The building, built in the 1970s, is an archetype of the modern, consumer lifestyle that Yugoslav market socialism promised to deliver to its citizens. Today the memories of a socialist moral economy are still present in the fabric of the building and the values of the residents who struggle to maintain their homes as individual spaces of comfort within a capitalist economy. This case shows the changing legitimacy of the pursuit of comfort and the ongoing tension to manage individual and collective gain.